Production and characterization of monoclonal antibodies to Clostridium perfringens enterotoxin. - Horiguchi, Y (1986)
Four hybridoma cell lines producing monoclonal antibodies to Clostridium perfringens enterotoxin were established by fusion of mouse myeloma and spleen cells obtained from mice immunized with the enterotoxin and its toxoid. An enzyme-linked immunosorbent assay indicated that the two antibodies, 2-B-4 and 3-G-10, bound to those regions that were located close each other; the others, 3-B-2 and 2-H-2, bound to other independent regions on the enterotoxin. Release of 51Cr from Vero cells with the enterotoxin was inhibited by either 2-B-4 or 3-G-10, both of which inhibited the binding of 125I-labeled enterotoxin to the cells. Neither binding nor cytotoxicity of the enterotoxin was affected by 2-H-2; 3-B-2 only barely inhibited the binding but neutralized the enterotoxin shown by 51Cr release. It seems justified to conclude that 3-B-2 blocks the toxic action after the enterotoxin has bound to Vero cells.